AJARAN TASAWUF SUNAN KALIJAGA DAN PENGARUHNYA BAGI PERKEMBANGAN PERTUNJUKAN WAYANG KULIT DI INDONESIA - Ariani, Iva (Fakultas Filsafat UGM, 2011)
The javanese society is a people that mostly embrace islamic religion. A history of islamic religion can not be released from influence and guardian from Wali Songo especially Sunan kalijaga. The influence of Sunan Kalijaga’s ideas scattered almost in all indonesian society’s life especially javanese society. This research is done to know the influence of Sunan Kalijaga’s ideas towards leather puppet’s culture developt in Indonesia. The things of course inseparable because leather puppet and Sunan Kalijaga’s ideas is the same big influential towards javanese society life. This research is a qualitative research that use book that explains Sunan Kalijaga’s ideas and other books that related to leather puppet world. This research produces a conclusion that leather puppet as a Javanese culture in this time development by Sunan Kalijaga’s ideas.